Persistent Diabetic Macular Edema: A Comprehensive Review of Current Treatments and Emerging Therapeutic Options - Shahin Faghihi; Hooshang Faghihi; Mir Alborz Faiez; Abbas Mohammadi; Esmaeil Asadi Khameneh; Elias Khalili Pour; Hamid Riazi-Esfahani (Journal of Current Ophthalmology)
Purpose: To comprehensively review and evaluate the therapeutic strategies for persistent diabetic macular edema (DME), with a particular emphasis on established treatments. Furthermore, the study explores emerging and innovative therapeutic options. Methods: A nonsystematic search was carried out using PubMed, Cochrane, Medline, and Google Scholar databases with the keywords “macular edema”, “persistent”, “diabetic”, “therapeutic”, and “emerging”. We specifically looked for experimental studies, randomized clinical trials, and retrospective and prospective studies without limiting the search timeframe for the articles up to December 2023. Results: This review delineates a comprehensive array of treatment modalities for persistent DME, encompassing anti-vascular endothelial growth factor (anti-VEGF) switching, corticosteroids, laser therapies, combination therapy, and surgical approaches. Additionally, emerging treatments were explored, featuring novel anti-VEGF agents, innovative surgical techniques, as well as inhibitors targeting Angiopoietin-2 and the Kallikrein–Kinin System. Conclusions: It is important to employ personalized and evidence-based approaches in addressing persistent DME. The ongoing advancement in treatment paradigms will play a crucial role in the continual evolution of DME management.